PENGEMBANGAN SISTEM INFORMASI PASIEN BERBASIS MOBILE PADA RSUD SUNAN KALIJAGA DEMAK DENGAN METODE WATERFALL - Muhamad Difa Khairuddin; Anita Fira Waluyo (LPPM Universitas Abdurrab, 2024)
through hard copies or manual records, requiring patients to prepare their data again for future medical visits. The absence of a mobile-based patient information system hinders public access to information due to its limited responsiveness. Therefore, a mobile-based patient information system is essential to optimize the quality of healthcare services by providing patients with their medical history and upcoming appointments for outpatient care. This research aims to create an online application for the registration process of outpatient and inpatient patients at RSUD, accessible through mobile devices, and to comprehend the existing patient visitation system at the hospital. The Waterfall methodology is employed for the development of the application in the patient information system of RSUD Sunan Kalijaga Demak. Observations and interviews serve as data collection methods. System testing is conducted using black box and Acceptance Testing involving potential user respondents to ensure the application functions effectively. The final outcome of this study is a mobile-based patient information system capable of managing patient data and medical records, thereby informing patients about their treatment history and upcoming appointments for outpatient care at RSUD Sunan Kalijaga Demak. Moreover, the user acceptance rate reaches an average of 84% based on the development of this patient information system.